Determination of ideal width for exclusive motorcycle lane along the straight section of Federal Highway, Selangor, Malaysia - Ahmad Rajabi, Mohammad Rasool (2012)
In the design of roadway, factors such as lane width, lateral clearance,vertical and horizontal alignment affects the capacity and Level-Of-Service (LOS). Ideal lane width is the upper limit range of width in which optimum capacity is achieved. There are numerous studies and literature available on the design of bicycle facilities. However, there are limited literature and studies about design of motorcycle facilities. The main issue pertaining to the provision of motorcycle facility is the width of its lane. If the width of the motorcycle lane is too wide, it may incur unnecessary construction costs and also leads to speeding problems. On the other hand, if the width of the lane is too narrow, the riding convenience and safety of motorcyclists may be affected particularly when overtaking is not possible. It is necessary to understand the basic sciences of motorcycles traffic so that a more scientific and professional judgment can be made with regard to the design and operation of motorcycle facilities. As such, this research aims to determine the effective factors affected by the motorcycle lane width, to establish relationship between these factors and finally determine the ideal width of motorcycle lane. Study sites which met the research criteria were selected along the existing exclusive motorcycle lane along the Federal Highway, Selangor, Malaysia. To observe motorcyclists riding and passing another motorcyclist within the motorcycle lane, the segments under study are at least 100 m long and covered lane widths ranging from 1.8 m to 3.3 m. Motorcycle flow was recorded using a digital video recorder and motorcycle count is obtained by transcribing the pre-recordings in the laboratory. Individual motorcycle spot speeds were measured using a laser speed detector. To observe motorcyclists riding comfort, transcription was done on the pre-recordings video in the laboratory where classification of comfortable or not comfortable used riding interruptions as a surrogate in the field. Aggregated motorcycle flow, speed and comfort data collected at 16 different motorcycle lane widths were plotted. Quadratic regression analysis was employed for the motorcycle flow-width relationship, Analysis of Variance (ANOVA) test for the motorcycle speed-width relationship, and logistic regression analysis for comfortable width. Results revealed that maximum motorcycle flow (mc/hr/m) occurs at 2.7 m wide lane, comfort is observed at 2.7 m lane or wider, and motorcycle speeds stabilized along 2.5 m lane or wider. Hence, 2.7 m is an ideal lane width for motorcycle lanes which encompassed the optimum of motorcyclist riding comfort, speed and flow. The findings of this study not only contribute new knowledge to the field of transportation engineering but would also be useful input in the design guidelines of motorcycle lanes for highly motorcycled countries.